The Role of Identity Motives on Quality of Life and Depressive Symptoms: A Comparison Between Young Adults With Multiple Sclerosis and Healthy Peers - Calandri, Emanuela; Graziano, Federica; Borghi, Martina; Bonino, Silvia; Cattelino, Elena (Frontiers in Psychology, 2020)
The diagnosis of a chronic illness during young adulthood represents a non-normative life transition influencing the identity definition process, as well as the individual psychological adjustment. The study examined if relationships between identity motives (self-esteem, efﬁcacy, continuity, distinctiveness, belonging, and meaning), health-related quality of life and depressive symptoms differ between healthy young adults and young adults diagnosed with multiple sclerosis (MS). 201 people (101 MS patients and 100 healthy controls), aged 18-35 years, completed a self-report questionnaire. Young adults with MS reported lower health-related quality of life and lower efficacy motive than their healthy peers. Among MS patients, high meaning was related to lower depressive symptoms, whereas high continuity and high belonging were related to higher health-related quality of life than in healthy controls. The study highlights the relevance of identity motives for the adjustment to MS and has implications for psychological interventions with young patients.